Sally Williams Fine Foods : getting to market - Townsend, Stephanie; Saini, Yvonne ([London] : SAGE, 2016)
Dries Pretorius, national sales manager of Sally Williams Fine Foods, a small manufacturer of luxury nougat, was furious. It was May 2007, four years since Sally Williams had first appointed its distributor and the thermostat at the distributor's warehouse had failed. As a result, his product had spoiled and he had to recall almost all of it. This was not the first mistake the distributor had made and Pretorius knew he had to make a change. Should Sally Williams bring distribution back in-house or continue to outsource it, he wondered. And if the decision was to outsource, what should the company look for in a new distributor?
Originally Published in: Townsend, S., & Saini, Y. (2008). Sally Williams Fine Foods: Getting To Market. WBS-2008-3. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on May 5, 2016).
Keywords: elektronické knihy; electronic books; Physical distribution of goods -- Case studies